A trophic niche shift in a South American migrant: Stable nitrogen isotope signatures in feathers of Fork-tailed Flycatchers (Tyrannus savana) - Macpherson, Maggie P.; Jahn, Alex E. [UNESP]; Defreitas, Justin; Looknauth, Kooldeep; Wilson, Asaph; Baird, Leon; Defreitas, Kayla; Chiasson, Susan; Taylor, Caz (Taylor & Francis, 2021)
Understanding how diet and life history strategies interact is important for exploring constraints of available nutrition on energetically expensive life history events in wild animals (i.e., reproduction, annual migration, molt). Previous research on migratory birds breeding in the Northern Hemisphere has demonstrated trophic niche shifts from invertebrates to fruit in order to fuel spring migration. We examined whether a trophic niche shift occurred in a Neotropical austral migrant, the Fork-tailed Flycatcher (Tyrannus savana savana), prior to spring migration by measuring stable nitrogen isotopes in feathers. We found that the austral migrant subspecies T. s. savana did appear to shift in diet from a higher to a lower trophic level (consistent in pattern with a shift from a higher to a lower ratio of invertebrates to fruit) but the shift occurred earlier than expected if it was preparation for migration. A sympatric sedentary subspecies occupying the same habitat (T. s. monachus) appeared to forage only at the lower trophic level during its annual molt and showed no evidence of a trophic niche shift; however, the molt of the 2 subspecies occurs at slightly different times of year. The timing of the trophic niche shift leads us to conclude that a higher trophic level diet early in molt is not related to preparation for spring migration but that it may be related to seasonal changes in food availability as the wet season concludes. A remaining challenge for understanding the ecological consequences of trophic niche shifts is to find ways to empirically measure trade-offs between different diets across energetically expensive life history events and compare these between taxa with differing life history strategies.
Keywords: flycatcher; migratory ecology; stable nitrogen isotope analysis